Reestructuración técnico administrativa en la empresa Beity S.A.S. (2017)
The technical and administrative restructuring of Beity S.A.S, dedicated to the manufacture, marketing and distribution of specialized furniture for the home directed to different user profiles, located in the city of Bogotá, is done with the purpose of making proposals for improvement in the processes of the Company to have a better competitiveness in the market.